2000
DOI: 10.1038/35017020
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular communication mediated by the extracellular calcium-sensing receptor

Abstract: Agonist-evoked, intracellular Ca2+-signalling events are associated with active extrusion of Ca2+ across the plasma membrane, implying a local increase in Ca2+ concentration ([Ca2+]) at the extracellular face of the cell. The possibility that these external [Ca2+] changes may have specific physiological functions has received little consideration in the past. Here we show that, at physiological ambient [Ca2+], Ca2+ mobilization in one cell produces an extracellular signal that can be detected in nearby cells e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
89
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(98 citation statements)
references
References 45 publications
9
89
0
Order By: Relevance
“…In almost all known cases Ca 2+ signaling is initiated by extracellular events or stimuli (Riccardi, 1999;Hofer et al, 2000) in communication with cell's plasma membrane. In a recent study, however, we showed that genetic or metabolic stress, specifically affecting mitochondrial Dc m , results in the activation of a novel type of Ca 2+ signaling in C2C12 myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In almost all known cases Ca 2+ signaling is initiated by extracellular events or stimuli (Riccardi, 1999;Hofer et al, 2000) in communication with cell's plasma membrane. In a recent study, however, we showed that genetic or metabolic stress, specifically affecting mitochondrial Dc m , results in the activation of a novel type of Ca 2+ signaling in C2C12 myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, treatment of monocytes with the p38 MAPK inhibitor SB203580 increased ERK1/2 activation, and this phosphorylation was blocked by the MEK inhibitor PD98059, indicating that there is also cross-talk between ERK1/2 and p38 MAPK in monocytes (42). Changes in extracellular calcium are monitored by the ubiquitously expressed extracellular calcium-sensing receptor (CaR) (43,44). Calcium-or agonist-induced activation of this G protein-coupled receptor has been linked to activation of various MAP kinases, including ERK1/2 (45)(46)(47).…”
Section: P38 Mapk Negatively Regulates Mmp-9 In Oral Cancermentioning
confidence: 99%
“…CASR has been reported to be widely expressed in several mammalian tissues, including tissues that are not clearly involved in Ca 2C metabolism such as brain, lens epithelial cells, pituitary gland, bone marrow, peripheral blood, breast ductal cells, pancreas, keratinocytes, ovarian surface epithelial cells, and the gastrointestinal system (reviewed by Brown et al (1993), McNeil et al (1998a), Hofer et al (2000), and Hofer & Brown (2003)). CASR localization in cells that seem to have no functional relationship with the maintenance of the whole-body Ca 2C balance has been linked to the regulation of different cellular processes, such as secretion, chemotaxis, apoptosis, cell proliferation, differentiation, and ion channel activity (for review see Hofer & Brown (2003)).…”
Section: Introductionmentioning
confidence: 99%